Cyberstalking on Social Media, How Does Islam View It? - Nurul Isnaini; Annisa Azzahro (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
With the development of information technology and the internet, social media has replaced real social relations with virtual ones. However, virtual social relations carry risks, one of which is Cyberstalking (Rohman & Sugeng 2022) Cyberstalking is a dangerous cybercrime and targets many people, communities, and organizations (Baer, 2020) As a crime, cyberstalking fulfills the elements of a criminal act which results in disruption of social order (Wall, 2007). Thus, cyberstalking is contrary to Islamic principles because it creates an insecure atmosphere. This research is library research using library materials in the form of books, journals, magazines, and other library sources as study material (Sukmadinata, 2010). Researchers will use a descriptive qualitative approach. Cyberstalking is a term used to describe various behaviors that involve repeated threats and/or harassment using electronic mail or other computer-based communications that will make people afraid or concerned for their safety (Gopalan, R.T. 2020). In Islam, these actions are prohibited acts because they contain elements of harassment, threats, harassment, or coercion. In interacting, Islam puts forward the concept of